DESALINATION OF THE BRACKISH WATER USING SURFACTANT MODIFIED ZEOLITE (SMZ) - Widi Astuti; Adil Jamali; Muhammad Amin (Jurnal Zeolit Indonesia, 2007)
The intrusion of seawater in the beach area of Bandar Lampung and the Eastern beach of Lampung causes many problems for people because it turns the water into a brackish water. The brackish water is the water whose salinity is between 0.5 ppt until 17 ppt. The brackish water cannot be used for drinking, cooking or washing because the maximum degree of salinity for such purposes is 0.5 ppt. Desalination of brackish water is a process of reducing the salinity of a brackish water. In this research, natural zeolite from Lampung was modified with surfactant to become surfactant-modified zeolite (SMZ). It was used as ion exchanger in the desalination of a brackish water. The result showed the salinity of the brackish water could be reduced to 52% from the initial value. The best results were obtained at the contact time of 4 hours and the initial salinity 0.863 ppt.